2022
DOI: 10.1038/s41541-022-00508-7
|View full text |Cite
|
Sign up to set email alerts
|

Optimized intramuscular immunization with VSV-vectored spike protein triggers a superior immune response to SARS-CoV-2

Abstract: Immunization with vesicular stomatitis virus (VSV)-vectored COVID-19 vaccine candidates expressing the SARS-CoV-2 spike protein in place of the VSV glycoprotein relies implicitly on expression of the ACE2 receptor at the muscular injection site. Here, we report that such a viral vector vaccine did not induce protective immunity following intramuscular immunization of K18-hACE2 transgenic mice. However, when the viral vector was trans-complemented with the VSV glycoprotein, intramuscular immunization resulted i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…SARS-CoV-2 pseudovirus neutralisation assay against the SARS-CoV-2 parental strain was performed as described using a green fluorescent protein reporter-based pseudotyped virus with a vesicular stomatitis virus backbone coated with SARS-CoV-2 spike protein. 12 Values above 23 BAU/mL and above a titre of 8 were considered positive for IgG and neutralising antibodies, respectively. Of all samples, 15% were randomly selected and assessed for T-cell activation; enzyme-linked immune absorbent spot was used to measure antigen-specific T cells that secrete IFN-γ.…”
Section: Methodsmentioning
confidence: 99%
“…SARS-CoV-2 pseudovirus neutralisation assay against the SARS-CoV-2 parental strain was performed as described using a green fluorescent protein reporter-based pseudotyped virus with a vesicular stomatitis virus backbone coated with SARS-CoV-2 spike protein. 12 Values above 23 BAU/mL and above a titre of 8 were considered positive for IgG and neutralising antibodies, respectively. Of all samples, 15% were randomly selected and assessed for T-cell activation; enzyme-linked immune absorbent spot was used to measure antigen-specific T cells that secrete IFN-γ.…”
Section: Methodsmentioning
confidence: 99%
“…Viral titers were expressed as 50% tissue culture infective dose per ml (TCID 50 /ml). Vesicular stomatitis virus (VSV) encoding green fluorescent protein (GFP) and expressing the C-terminally truncated spike protein of SARS-CoV-2 (VSV*ΔG-S Δ21 ) was previously described [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…Since the beginning of the pandemic, different VSV based vaccine vectors expressing spike protein (full length or truncated) have been studied and shown to protect hamsters and mice from SARS-CoV-2 infection by inducing a strong immunity 29 35 . Two of these VSV based vaccine vectors expressing spike protein led to clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…The potential that minimal expression of ACE2, the cellular receptor for SARS-CoV-2 spike, is found on the surface of skeletal muscle cells 19 , 21 may greatly reduce the efficiency of a VSV-SARS-CoV-2 spike vaccine such as V590 when administered intramuscularly. A recent study by Taddeo et al 29 showed an optimized and enhanced IM route of VSV based viral vector spike vaccination using trans-complemented with the VSV-G glycoprotein. VSV-G is known to have broad tissue tropism.…”
Section: Discussionmentioning
confidence: 99%